Investigation of the activity of baicalein towards Zika virus - Suteema Sawadpongpan; Janejira Jaratsittisin; Atitaya Hitakarun; Sittiruk Roytrakul; Nitwara Wikan; Duncan R. Smith (BMC, 2023)
Abstract Background Zika virus (ZIKV) is a mosquito transmitted virus spread primarily by Aedes species mosquitoes that can cause disease in humans, particularly when infection occurs in pregnancy where the virus can have a significant impact on the developing fetus. Despite this, there remains no prophylactic agent or therapeutic treatment for infection. Baicalein is a trihydroxyflavone, that is found in some traditional medicines commonly used in Asia, and has been shown to have several activities including antiviral properties. Importantly, studies have shown baicalein to be safe and well tolerated in humans, increasing its potential utilization. Methods This study sought to determine the anti-ZIKV activity of baicalein using a human cell line (A549). Cytotoxicity of baicalein was determined by the MTT assay, and the effect on ZIKV infection determined by treating A549 cells with baicalien at different time points in the infection process. Parameters including level of infection, virus production, viral protein expression and genome copy number were assessed by flow cytometry, plaque assay, western blot and quantitative RT-PCR, respectively. Results The results showed that baicalein had a half-maximal cytotoxic concentration (CC50) of > 800 µM, and a half-maximal effective concentration (EC50) of 124.88 µM. Time-of-addition analysis showed that baicalein had an inhibitory effect on ZIKV infection at the adsorption and post-adsorption stages. Moreover, baicalein also exerted a significant viral inactivation activity on ZIKV (as well as on dengue virus and Japanese encephalitis virus) virions. Conclusion Baicalein has now been shown to possess anti-ZIKV activity in a human cell line.